Colombia - Lessons from the Competitive Allocation of Research Funding in the Agricultural Sector - Cristancho, Edwin (World Bank, Washington, DC, 2012)
Since 2004, Colombia's ministry of agriculture and rural development has implemented a strategy of competitive funding or public call for proposals for the allocation of public funds for Research, Technological Development and Innovation (RTDI) programs and projects targeting the agricultural sector. This strategy considers science and technology as core elements of agricultural sector policy, and the allocation of funds is governed by principles of cost-effectiveness and transparency. The fact that Latin American (LAC) countries, especially Colombia, are commonly endowed with a high concentrations of biodiversity (habitats and species) compared to other regions of the world, generates significant opportunities for RTDI. These projects offer a systematic way of making use of biodiversity in life sciences aimed at solving problems (e.g. a new disease-resistant variety of a traditional crop) or generating commercial returns (e.g. a native fruit that can be domesticated, harvested and industrialized). Moreover, proposals were typically submitted by research entities (universities and research centers) that were often disconnected from the needs of the productive sector and which often generated results scarcely relevant to producers.